PENGARUH OWNERSHIP, INDEPENDENT BOARD DAN FIRM SIZE TERHADAP KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Yefri Reswita; Rida Rahim (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
Banking companies are companies that provide financial services for all levels of society. Over time, the company developed to follow the market demand so that most companies listed their stocks in Indonesia Stock Exchange to obtain additional capital. Of course, with this decision, the company will be owned by investors so that each investor has their respective interests. This study deals with knowing the commitment of independent commissioners, share ownership either insiders (Commissioners, Directors) or outsiders (institutional) to the financial performance measured by Return on Assets (ROA) and Tobins'Q. The control variable that is utilized is Firm Size. The sample that is used in this study was 200 banking companies listed on the Indonesia Stock Exchange. The analysis used is multiple regression analysis with SPSS application. This study proves that the share ownership of both insiders and outsiders does not affect either the Return on Assets (ROA) or the value of Tobins'Q. Independent board has a significant effect on Return on Assets (ROA), and on Tobins'Q value. While  firm size affects the Return on Assets (ROA) but does not affect Tobins'Q value.